Analysis and evaluation of the United Kingdom and Spain`s sport models - Puga-González, E.; Torres-Luque, G.; González-Ruiz, J.; Cabello-Manrique, D. (Journal of Human Sport & Exercise, 2019)
In this study, we have undertaken an analysis of the status of Spanish and British sport models. Sport has become a major socio-economic marvel of the modern world, with broad media coverage and both active and passive participation. Sporting achievement, the public image of many countries, is a top priority for the governments of developed nations and represents a goal of general interest. Using data analysis, we have examined the reality of the sport models in both countries through sportive variables, as well as the financials behind the sporting economy in the last 5 Olympic Games. The data reveals a more efficiency model in UK and a need of change if Spain wants to keep its current level of achievement internationally, where the current model requires a review of its structure and funding sources, public or private, and the modernisation of the federated management model that must be preserved and encouraged through (non-profit) organisations that benefit from a favourable tax system, such as the Sports Federations.